1995
DOI: 10.1177/030802269505800704
|View full text |Cite
|
Sign up to set email alerts
|

Minority Ethnic Groups and Occupational Therapy, Part 2: Transcultural Occupational Therapy, a Curriculum for Today's Therapist

Abstract: This article is the second of two contributions looking at the under-representation of people from the United Kingdom's minority ethnic groups in the occupational therapy profession. These articles suggest three broad areas that should concern occupational therapy practitioners and educators; the recruitment of people from minority ethnic groups to the profession; the admission process to occupational therapy education and training courses; and the curriculum and ethos of those courses. Part 2 deals with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Comprehensive curricula as proposed by Kinebanian and Stomph (1992) and MacDonald and Rowe (1995) aiming to develop cultural understanding and sensitivity of occupational therapy students toward different ethnic groups are of importance to the profession. Sue (1991) suggests that training programmes should contain an awareness and knowledge component (for example, lectures and readings on a variety of cultures), an affective component (for example, debriefing and reflecting regarding feelings of another culture through informal discussion), and a skills component (for example, an in-depth personal interaction with another culture for an extensive period of time).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive curricula as proposed by Kinebanian and Stomph (1992) and MacDonald and Rowe (1995) aiming to develop cultural understanding and sensitivity of occupational therapy students toward different ethnic groups are of importance to the profession. Sue (1991) suggests that training programmes should contain an awareness and knowledge component (for example, lectures and readings on a variety of cultures), an affective component (for example, debriefing and reflecting regarding feelings of another culture through informal discussion), and a skills component (for example, an in-depth personal interaction with another culture for an extensive period of time).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural competency has been widely discussed in a variety of heath care disciplines including nursing, social work and occupational therapy (Caple, Salcido & di Cecco, 1995;Dillard, et al, 1992;Macdonald & Rowe, 1995;Manoleas, 1994;Pope-Davis, Prieto, Whitaker & Pope-Davis, 1993;Ronnau, 1994). Dillard et al define cultural competency as "an awareness of, sensitivity to, and knowledge of the meaning of culture" (1992, p. 722).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Krefting and Krefting (1991) stated that culture had an endless list of basic elements, 'law, customs, goals, beliefs, values etc' (p102) and that ethnicity was an important component. According to Macdonald and Rowe (1995), if the influence of culture is not considered by the occupational therapist, there will be an enormous effect upon assessment and intervention.…”
Section: Background Culturementioning
confidence: 99%
“…Often, in ISO societies, the beliefs, family structure and respect for elders are more important than independence. Macdonald and Rowe (1995) suggested that concepts related to independence were linked to Western middleclass values and that it might be more appropriate to consider the tasks and roles of family members. An elderly disabled person might not aim for or accept the concept of being independent because the family members were duty bound to help him or her (Kinebanian and Stomph, 1992).…”
Section: Health Beliefsmentioning
confidence: 99%